A=P(1+rt)

Rewrite the equation as P(1+rt)=A.

P(1+rt)=A

Divide each term in P(1+rt)=A by P.

P(1+rt)P=AP

Cancel the common factor of P.

Cancel the common factor.

P(1+rt)P=AP

Divide 1+rt by 1.

1+rt=AP

1+rt=AP

1+rt=AP

Subtract 1 from both sides of the equation.

rt=AP-1

Divide each term in rt=AP-1 by r.

rtr=AP⋅1r+-1r

Cancel the common factor of r.

Cancel the common factor.

rtr=AP⋅1r+-1r

Divide t by 1.

t=AP⋅1r+-1r

t=AP⋅1r+-1r

Simplify each term.

Multiply AP and 1r.

t=APr+-1r

Move the negative in front of the fraction.

t=APr-1r

t=APr-1r

t=APr-1r

Solve for t A=P(1+rt)